Ultizing Team Games Tournament Method to Enchance Learning Outcomes on Islamic Studies at Elementary School - Widiyanti, Endang; Rahman, Asep Andi (Jurnal Keprofesian Guru Keagamaan, 2024)
This study aims to improve student learning outcomes in Islamic Religious Education (PAI) subjects on Fathu Makkah material in class V of SDN 064 Padasuka using the Team Games Tournament (TGT) method. The TGT method, as a cooperative learning model, involves student collaboration through group games and tournaments to increase active participation and student understanding of the material. This study uses a Classroom Action Research (CAR) design consisting of two cycles, each with stages of planning, implementation, observation, and reflection. The research subjects were 30 students. Data collection was carried out through learning outcome tests, observation sheets, and documentation. The results of the study showed a significant increase in student learning outcomes, with learning completeness reaching 70% in cycle I and increasing to 85% in cycle II. In addition, the TGT method also increases student involvement and motivation in learning. Thus, this method is effective in improving learning outcomes in PAI learning.